Lack of an inverse association between tuberculosis infection and atopy: By T-cell-based immune assay (RD1-ELISpot) - (:unkn) unknown (WILEY, 2008)
The association between mycobacterial exposure, vaccination with bacillus Calmette-Guerin (BCG) in early life and atopy remains controversial. Distinguishing between environmental mycobacterial exposure, TB infection and BCG-vaccination is not possible with the tuberculin skin test (TST) but new accurate blood-tests for TB infection present an opportunity to differentiate TB infection from environmental mycobacterial exposure and BCG-vaccination. We used a new blood test in parallel with TST to investigate whether Mycobacterium tuberculosis infection and/or BCG vaccination are associated with development of atopy in children with prior household TB contacts. All children who had contact with adult active pulmonary TB during the last 6 months underwent TST, chest radiography, and RD1-ELISpot assay. The presence of a BCG scar was documented, and assessment of atopy was carried out by International Study of Asthma and Allergies in Childhood questionnaire, allergy skin prick testing (SPT) and evaluation of serum total IgE. Among 361 children enrolled 39 (11%) had a positive SPT, 236 (63%) positive TST, and 189 (52%) positive RD1-ELISpot. The frequency of SPT positivity, ever wheezing, allergic rhinitis, doctor-diagnosed asthma, high serum IgE level, and median total serum IgE levels did not differ significantly different by TST or RD1-ELISpot status. On the other hand, presence of BGC scar was associated with lower median total serum IgE level (p = 0.01) and lower frequency of high IgE (p = 0.003). M. tuberculosis infection whether measured by TST or RD1-ELISpot, was not associated with atopy in children with household TB contact. Presence of a BCG vaccination scar was inversely associated with atopy, as measured by serum IgE.
Keywords: Mycobacterium tuberculosis infection; tuberculin skin test; RD1-ELISpot assay; skin prick test; atopy; BACILLUS-CALMETTE-GUERIN; DELAYED-TYPE HYPERSENSITIVITY; EARLY BCG VACCINATION; SKIN-TEST; CHILDREN; RESPONSES; ASTHMA; BOVIS; ENUMERATION; POPULATION